Regional differences in human ependymal and subventricular zone cytoarchitecture are unchanged in neuropsychiatric disease. - Comte, I; Kotagiri, P; Szele, F (2012)
Much work has focused on the possible contribution of adult hippocampal neurogenesis to neuropsychiatric diseases. The hippocampal subgranular zone and the other stem cell-containing neurogenic niche, the subventricular zone (SVZ), share several cytological features and are regulated by some of the same molecular mechanisms. However, very little is known about the SVZ in neuropsychiatric disorders. This is important since it surrounds the lateral ventricles and in schizophrenia ventricular enlargement frequently follows forebrain nuclei shrinkage. Also, adult neurogenesis has been implicated in pharmacotherapy for affective disorders and many of the molecules associated with neuropsychiatric disorders affect SVZ biology. To assess the neurogenic niche, we examined material from 60 humans (Stanley Collection) and characterized the cytoarchitecture of the SVZ and ependymal layer in age-, sex- and post mortem interval-matched controls, and patients diagnosed with schizophrenia, bipolar illness, and depression (n = 15 each). There is a paucity of post mortem brains available for study in these diseases, so to maximize the number of possible parameters examined here, we quantified individual sections rather than a large series. Previous work showed that multiple sclerosis is associated with increased width of the hypocellular gap, a cell-sparse region that typifies the human SVZ. Statistically there were no differences between disease groups and controls in the width of the hypocellular gap or in the density of cells in the hypocellular gap. Because ventricular enlargement in schizophrenia may disrupt ependymal cells, we quantified them, but observed no difference between diagnostic groups and controls. There are significant differences in the prevalence of neuropsychiatric illness between the sexes. Therefore, we looked for male versus female differences, but did not observe any in the parameters quantified. We next turned to a finer spatial resolution and asked if there were differences amongst the disease groups in dorsal ventral subdivisions of the SVZ. Similar to when we treated the SVZ as a whole, we did not find such differences. However, compared to the dorsal SVZ, the ventral SVZ had a wider hypocellular gap and more ependymal cells in all four groups. In contrast, cell density was similar in dorsal ventral subregions of the SVZ hypocellular gap. These results show that though there are regional differences in the SVZ in humans, neuropsychiatric disorders do not seem to alter several fundamental histological features of this adult neurogenic zone.